2016
DOI: 10.1259/bjr.20160374
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stereotactic radiotherapy for brain metastases using dynamic jaws technology in the helical tomotherapy system

Abstract: Objective:Dynamic jaws (DJ) are expected to be useful in stereotactic radiotherapy (SRT) for brain metastases (BM). The efficacy and optimal dose fractionation were investigated.Methods:In a planning study, 63 treatment plans were generated for the following 3 conditions: 1.0-cm fixed jaws (FJ), 2.5-cm FJ and 2.5-cm DJ. In a clinical study, 30 Gy/3 fr, 35 Gy/5 fr or 37.5 Gy/5 fr were prescribed depending on tumour size. Clinical results of groups treated with 2.5-cm DJ plans and 1.0-cm FJ were compared.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…But no significant differences in dose distribution, clinical efficacy and toxicity were observed in study [5]. Thus, this technology is most useful in SRT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…But no significant differences in dose distribution, clinical efficacy and toxicity were observed in study [5]. Thus, this technology is most useful in SRT.…”
Section: Discussionmentioning
confidence: 82%
“…At least, 95% of the PTV volume must be covered by 95% of the prescribed dose, if OAR is partially or fully included in PTV, and there is no possibility to irradiate it with the full prescribed dose [5]. Each individual case is always discussed with a therapist.…”
Section: Preliminary Assessment Planmentioning
confidence: 99%
“…Even if the phase II trial is positive (i.e., p < 0.20), that is not considered conclusive without a subsequent phase III trial. The results of the previous study of irradiation at intervals demonstrated a 1-year IC-LC of 93% [ 13 ]. Assuming a 1-year IC-LC of 70% for Arm 1 (consecutive daily irradiation) and 90% for Arm 2 (irradiation at two- to three-day intervals) and a 1-year OS of 50% for target patients, with 80% power, alpha of 0.20, an 5% lost follow-up rate, accrual time of 4 years and a total trial time of 5 years, 70 patients will be required (35 in Arm 1 and 35 in Arm 2).…”
Section: Discussionmentioning
confidence: 99%
“…The jaws open up and close down from/to a minimal value of 1 cm at the beginning and end of the treatment, with the fixed nominal jaw width in between to reduce longitudinal dose penumbra. [19][20][21][22][23][24][25] Several additional delivery features are available on the Radixact delivery system. 26 While the jaw settings and gantry periods remain the same, the nominal dose rate of Radixact has increased from 850 to 1000 cGy/min.…”
Section: New Delivery and Imaging Modalities (With Hardware Enhanceme...mentioning
confidence: 99%